Positive Fictitious Lawsuits in the Digital Era: Challenges Executing Administrative Court Decisions in OSS - Saan Saan; Tubagus Ahmad Ramadan (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2026)
The introduction of the positive fictitious doctrine through Law Number 30 of 2014 concerning Government Administration is a significant effort to realize legal certainty for the public regarding the silence of bureaucratic authorities. However, the transformation of public services into the Online Single Submission (OSS) system after the Job Creation Law has created a new legal paradox. This study aims to analyze the legal implications of the OSS system on positive fictitious procedures and identify obstacles in executing Administrative Court (PTUN) decisions against algorithm-based systems. Using a normative legal research method with a statutory and conceptual approach, this study finds that the digitalization of bureaucracy tends to reduce official discretion, which is a core element in the Residue Theory. A crucial problem arises when PTUN decisions that have permanent legal force cannot be accommodated by the rigid and automated algorithms of the OSS system, thereby creating legal uncertainty. This study concludes the need for legal reconstruction through the synchronization of the Supreme Court's E-Court system with the OSS system, as well as updating procedural regulations to ensure the effectiveness of decision execution in the era of smart governance.